O processo inovativo e o papel das instituições no arranjo produtivo de móveis da serra gaúcha - Lopes, Manuela Francisca (Universidade do Vale do Rio do Sinos, 2008)
The main objective of the present study is to verify the influence of the institutions on innovative capacity of “Local Productive Arrangement” (LPA) of furniture industry in the mountains (sierra) of Rio Grande do Sul state. In order to make this study possible, a characterization of the arrangement was done, highlighting the behaviour of those furniture companies, as well as the role of institutions linked to this “manufacturing activity”. Furthermore, interviews were applied in the city of Bento Gonçalves, with representatives of those selected companies, representatives of research and teaching institutions as well as with associations and “sector entities”. The emphasis given to the city of Bento Gonçalves, is due to the fact that this region (mountains of Rio Grande do Sul state) concentrates most of the activities linked to furniture industry. This study is focused on the way that the mentioned companies have been using the available infrastructure and also on to what extent this interactivity has be
Keywords: capacitação tecnológica; cooperação; indústria moveleira; Rio Grande do Sul; arranjo produtivo local; furniture industry; local productive arrangement; technological capability; Ciências Sociais Aplicadas